2021
DOI: 10.5603/imh.2021.0051
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an on-board psychosocial programme on stress, resilience, and job satisfaction amongst a sample of merchant seafarers

Abstract: This article is available in open access under Creative Common Attribution-Non-Commercial-No Derivatives 4.0 International (CC BY-NC-ND 4.0) license, allowing to download articles and share them with others as long as they credit the authors and the publisher, but without permission to change them in any way or use them commercially.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Previous studies showed that a variety of stressors in seafaring may result in poorer physical health and a higher prevalence of anxiety, depression, and somatization (33). Therefore, interventions aimed at changing work conditions (34), as well as programs that strengthen individual resources (35) need to be promoted. It can be hypothesized whether ship familiarization is a possible source of stress on board as it is an important part of the onboarding process in seafaring organizations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that a variety of stressors in seafaring may result in poorer physical health and a higher prevalence of anxiety, depression, and somatization (33). Therefore, interventions aimed at changing work conditions (34), as well as programs that strengthen individual resources (35) need to be promoted. It can be hypothesized whether ship familiarization is a possible source of stress on board as it is an important part of the onboarding process in seafaring organizations.…”
Section: Discussionmentioning
confidence: 99%
“…There is a body of studies among seafarers that have identified different determinants of job satisfaction, such as resilience, 57 psychological capital, 61 and personal hardiness, 62 so it is crucial to apply secondary-level interventions that are likely to contribute to better stress coping skills. 63 Being able to cope with stress reduces possible burnout 64 and improves psychological well-being. 65 Besides different occupational stress interventions tailored to the individual level, it is a top-priority for seafaring organizations to plan and implement primary-level interventions which reduce or remove external stressors such as long working hours that disrupt circadian rhythm.…”
Section: Discussionmentioning
confidence: 99%
“…12,35,36 Suicide among seafarers and abandonment of seafarers by ship owners during this pandemic remains a serious but generally publicly unknown issue. [37][38][39][40] Except for one study, 12 none of the literature cited has investigated how seafarers are the sources of psychosocial support of their fellow crewmember during this pandemic. The above discussion demonstrates a gap in the literature on empowerment of seafarers as agents of MH for themselves and their peers.…”
Section: Mh Of Seafarers In Recent Literaturementioning
confidence: 99%